Analisis Kinerja Petugas Boarding Gate Pada PT Kokapura Dalam Mencapai On Time Performance (OTP) Di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Dewi Safitri; Kifni Yudianto (CV. Aksara Global Akademia, 2023)
On Time Performance is very important for the image of an airline company. The performance of boarding gate officers is one of main factors in creating On Time Performance during the brading process it is also necessary to have quality human resource support god service to passangers. Gate officers must be careful and coordinae with other staff in carrying out boarding. Analysis of the performance of gate officers in achieving an On Time Performance flight based on performance indicators. To analyze the data in this study using descriptive qualitative methods. Reserch data collection was carried out by means of interviews, observation, documentation and literature studies in the boarding gate work unit area of PT Kokapura Jenderal Ahmad Yani Airport, Semarang. The result of this study are the performance of boarding gate officers who are quite good at providing boarding services to passanger. Boarding gate officers carry out boarding activities in accordance with the Standart Operational Procedure (SOP) that applies to each airline handled by PT Kokapura Ahmad Yani. The obstacle experienced by gate officers was the lack of information regarding flight delays, however, gate officers were able to overcome these obstacles bycoordinating and updating every 10 minutes with operational staff regarding the condition of the aircraft to be boarded.